2018
DOI: 10.3390/molecules23071654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dibutyltin Dilaurate on Triglyceride Metabolism through the Inhibition of the mTOR Pathway in Human HL7702 Liver Cells

Abstract: Dibutyltin dilaurate (DBTD) has multiple applications in daily life. However, DBTD is easily deposited in the liver and affects liver functions. This study was designed to explore the effects of DBTD on triglyceride metabolism in human normal hepatocyte HL7702 cells. Our results showed that the intracellular fat contents were dose-dependently decreased by DBTD. The expression of lipolysis genes and proteins were elevated while the lipogenesis genes and proteins were diminished by DBTD. The phosphorylation leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…11 However, tin-based compounds and organotin compounds, such as DBTDL in particular, exhibit cytotoxicity, 12 are difficult to remove from polymers, and have adverse environmental effects. 13 Therefore, their usage in medical applications is limited 14 and there is growing interest in "greener" organotin-free reaction pathways. 15 Towards this aim, alternative catalytic systems are being explored that replace tin with other metals, such as zinc, titanium, zirconium, manganese, etc.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, tin-based compounds and organotin compounds, such as DBTDL in particular, exhibit cytotoxicity, 12 are difficult to remove from polymers, and have adverse environmental effects. 13 Therefore, their usage in medical applications is limited 14 and there is growing interest in "greener" organotin-free reaction pathways. 15 Towards this aim, alternative catalytic systems are being explored that replace tin with other metals, such as zinc, titanium, zirconium, manganese, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have suggested that traditional Chinese medicines exert beneficial effects via modulation of the transcription of related genes . To date, several genes have been reported to be the downstream effectors of schizandrin, including hefA and thymic stromal lymphopoietin .…”
Section: Discussionmentioning
confidence: 99%
“…The decreased expression levels of cluster of differentiation 36 (CD36), fatty acid binding protein 4 (FABP4), enoyl-CoA hydratase and 3-hydroxyacyl CoA dehydrogenase (EHHADH), acetyl-CoA acyltransferase 1 (ACAA1), phosphoenolpyruvate carboxykinase (PEPCK), PPARα, and PPARγ in DBDCT-treated liver tissue were indicated by proteomics. Furthermore, the toxic effect was alleviated by PPARγ blocking agent T0070907 [42,43]. Additionally, organotins, the major components of agricultural fungicides and pesticides, were documented to exert similar functions as PPARγ and PPARβ ligands, which promote weight gain and increase fat storage by target gene induction in liver [44].…”
Section: Ppars In Hepatotoxicitymentioning
confidence: 99%